2018
DOI: 10.1007/s00296-018-4195-x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment patterns, unmet need, and impact on patient-reported outcomes of psoriatic arthritis in the United States and Europe

Abstract: Psoriatic arthritis (PsA) is a chronic, inflammatory disease. The effects of PsA real-world treatment patterns on patient-reported outcomes in the US and 5 European countries (EU5; France, Germany, Italy, Spain, UK) were evaluated. Respondents from the 2016 National Health and Wellness Survey received advanced therapies (e.g., biologic disease-modifying antirheumatic drugs [DMARDs]), other therapies, (e.g., conventional synthetic DMARDs), or no treatment. Assessments included demographics, disease severity (pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 47 publications
3
16
0
Order By: Relevance
“…This finding is consistent with a report that overall employment rates are significantly lower in patients with rheumatic diseases than in the general population, especially in those with ankylosing spondylitis and PsA. [33][34][35] Unemployment and work impairment, including time away from work (absenteeism) or reduced effectiveness at work (presenteeism), affects up to 50% of people with PsA. 6 A National Psoriasis Foundation (US) survey found that 49% of respondents routinely missed work due to psoriasis or PsA, with more than 10 workdays per month missed by 31% of those respondents.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with a report that overall employment rates are significantly lower in patients with rheumatic diseases than in the general population, especially in those with ankylosing spondylitis and PsA. [33][34][35] Unemployment and work impairment, including time away from work (absenteeism) or reduced effectiveness at work (presenteeism), affects up to 50% of people with PsA. 6 A National Psoriasis Foundation (US) survey found that 49% of respondents routinely missed work due to psoriasis or PsA, with more than 10 workdays per month missed by 31% of those respondents.…”
Section: Discussionsupporting
confidence: 93%
“…37 Our analysis showed that patients with PsA have lower SF-36 physical and mental scores and lower health-related QoL scores compared with the general population. 38 In a study conducted by Gottlieb et al, 39 SF-36 PCSs in patients with PsA were similar to the ones reported in the literature, while the SF-36 MCSs were lower. In a study conducted in the general population in Norway, a comparison of patients with PsA using bDMARD with those using csDMARD revealed that the scores for the bodily pain, vitality, physical role, and general health perception subscales of SF-36 showed greater improvement.…”
Section: Discussionsupporting
confidence: 65%
“…switching or adding therapies for patients with inadequately controlled symptoms). Treatment adherence and persistence to biologic therapies is an important determinant of patient outcomes in rheumatic diseases, including PsA 7,8 . A recent administrative claims database study of patients with PsA found that less than half of patients who newly initiated a biologic were persistent with their index TNF or IL-12/23 inhibitor during a 1-year follow-up period 9 .…”
Section: Introductionmentioning
confidence: 99%